Molecular and cellular analysis of MSC-EPO-mediated protection of degenerating retinas - Koh, Avin Ee Hwan (2021)
The retina is a multi-layered tissue that functions to provide vision. Because of its complexity, a dysfunction in any layer can lead to retinal degeneration and various degrees of visual impairment. Such cases are imminent, and current treatments can only delay the disease onset. In order to restore the degenerating retina, stem cells can be introduced. Mesenchymal stem cells (MSC) have been heralded as a potential cure due to its multipotent differentiation and cellular reparative capabilities, as shown in numerous clinical studies. However, there were also contradicting findings that revealed a worse prognosis for blindness after MSC transplantation. Such variable results are due to the limitations of MSC therapy. For example, donor cell heterogeneity, epigenetic modifications, and health status can have a huge impact on MSC efficacy. These limitations can be tackled by genetically-modifying MSCs to express exogenous growth factors that enhance the survivability of transplanted MSCs and the surrounding tissue. Erythropoietin (EPO) is a potential enhancer. Apart from being involved in erythropoiesis, EPO plays another role in anti-apoptosis and neuroregeneration by binding to EPO-receptors on non-erythroid cells like the retina. In this study, the novel synergistic interactions between MSC and EPO were explored in the form of human EPO-expressing MSCs (MSCsEPO) to evaluate its therapeutic potential in recovering the retina of a rodent model of retinal degeneration. Firstly, this was tested in an in vitro model of retinal cell toxicity. ARPE-19 cytotoxicity was induced with a retinotoxin known as sodium iodate (NaIO3) and treated with conditioned media (CM) from MSCs or MSCsEPO. Subsequent cell viability assays performed using MTT and flow cytometry revealed statistically significant increases in ARPE-19 survivability at 24 h and 48 h post-treatment (P <0.05). Furthermore, MSCEPO-CM treatment was shown to be statistically significant in the early phase of the treatment (24 h). However, both MSC and MSCEPO-CM treatments were comparable at 48 h. After performing the proof of concept study in vitro, the study proceeded to in vivo experimentation. After an initial optimization with various doses of systemically-administered NaIO3 (20 – 80 mg/kg) in Sprague-Dawley rats, it was found that 40 mg/kg was the ideal dose to trigger moderate retinal degeneration (around 50%). This was assessed using histo-anatomical methods and electroretinography (ERG), which revealed the degenerated retinal layers and attenuated ERG graphs. After successfully developing the model, an intravitreal transplantation of MSCsEPO was performed, and the model was assessed using similar techniques. The results showed that after day 30, both the MSC and MSCEPO treatment groups exhibited improved visual functions compared to the sham control (P <0.05). Although MSCs were able to protect visual function, MSCsEPO showed comparable results with MSCs. A further in-depth investigation using RNA sequencing revealed a set of pro-survival gene expressions. Most notably, MSCEPO was found to activate the phototransduction pathway. The PI3K-Akt signaling pathway, a downstream EPO activator, was also significantly activated by MSCEPO. The transcriptomics profile showed a clear, positive correlation with the functional data from the treated groups. Interestingly, several immune response pathways were upregulated in the MSC group but not MSCsEPO. Further studies are required to investigate the functional implications of this expression profile on immunomodulation. Taken together, this study has shown that treatment with MSCs conferred pro-survival benefits to retinal cells as well as protection against retinal degeneration. On the other hand, MSCsEPO showed comparable results with MSCs and hence, was not significantly better. Still, these results may be utilized in future studies to further investigate MSCEPO therapy for retinal diseases.